Hepatitis C Virus Infection and Kidney Transplantation in 2014: What's New?. Issue 10 (4th August 2014) - Baid‐Agrawal, S.; Pascual, M.; Moradpour, D.; Somasundaram, R.; Muche, M.
<x xml:space="preserve">Abstract</x> Chronic hepatitis C virus (HCV) infection remains an important health problem, which is associated with deleterious consequences in kidney transplant recipients. Besides hepatic complications, several extrahepatic complications contribute to reduced patient and allograft survival in HCV‐infected kidney recipients. However, HCV infection should not be considered as a contraindication for kidney transplantation because patient survival is better with transplantation than on dialysis. Treatment of HCV infection is currently interferon‐alpha (IFN‐α) based, which has been associated with higher renal allograft rejection rates. Therefore, antiviral treatment before transplantation is preferable. As in the nontransplant setting, IFN‐free treatment regimens, because of their greater efficacy and reduced toxicity, currently represent promising and attractive therapeutic options after kidney transplantation as well. However, clinical trials will be required to closely evaluate these regimens in kidney recipients. There is also a need for prospective controlled studies to determine the optimal immunosuppressive regimens after transplantation in HCV‐infected recipients. Combined kidney and liver transplantation is required in patients with advanced liver cirrhosis. However, in patients with cleared HCV infection and early cirrhosis without portal hypertension, kidney transplantation alone may be considered. There is some agreement about the use of HCV‐positive donors in HCV‐infected recipients, although data regarding posttransplant survival rates are controversial.